Femtosecond free-electron laser x-ray diffraction data sets for algorithm development - Kassemeyer, Stephan; Steinbrener, Jan; Lomb, Lukas; Epp, Sascha W.; Erk, Benjamin Michael Dieter; Foucar, Lutz Michael; Rolles, Daniel; Rudek, Benedikt; Rudenko, Artem; Shoeman, Robert L.; Ullrich, Joachim; Schlichting, Ilme (Optics express, 2012)
We describe femtosecond X-ray diffraction data sets of viruses and nanoparticles collected at the Linac Coherent Light Source. The data establish the first large benchmark data sets for coherent diffraction methods freely available to the public, to bolster the development of algorithms that are essential for developing this novel approach as a useful imaging technique. Applications are 2D reconstructions, orientation classification and finally 3D imaging by assembling 2D patterns into a 3D diffraction volume.
Published 3 Feb 2012
Gesehen am 19.09.2018